2017
DOI: 10.1186/s40173-017-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Pension schemes and labor supply in the formal and informal sector

Abstract: This paper analyzes the participation path of workers in the formal and informal sectors throughout their lives and their pension eligibilities, as well as how the social security scheme can change the aforementioned participation path. High levels of informality have impacts on the benefits that workers receive, especially their pension benefits. I use Argentinean panel data from 1995 to 2008 to construct a structural discrete choice model which estimates the population's labor path and their pension eligibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The state of the labor market is the main factor affecting the efficiency of the pension system [50][51][52][53]. Therefore, the indicators of the labor market for 2014-2019 were used as independent variables affecting the forecast indicators of the Kazakhstani pension system efficacy in the context of regions and cities in the Republic of Kazakhstan in line with [15].…”
Section: Methodsmentioning
confidence: 99%
“…The state of the labor market is the main factor affecting the efficiency of the pension system [50][51][52][53]. Therefore, the indicators of the labor market for 2014-2019 were used as independent variables affecting the forecast indicators of the Kazakhstani pension system efficacy in the context of regions and cities in the Republic of Kazakhstan in line with [15].…”
Section: Methodsmentioning
confidence: 99%
“…When their needs are met, they may be more motivated to contribute productively to the enterprise's performance. Ceni (2017) stated that a forceful pension ensures a worker's satisfaction and dedication to the firm throughout his or her working time. Similarly, Salah et al (2019) also suggested that contributory pension schemes are an essential management approach to improve worker engagement and job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite their socioeconomic significance, SMEs have a variety of obstacles. According to Ceni (2017), one of the fundamental features of developing-country labor markets is the insufficiency of pension contributions from firms and employees. This characteristic impacts not only the current condition of employees who are not entitled to advantages such as medical care, unemployment insurance, or additional grants but also admission to the pension scheme for the aged.…”
Section: Implications and Recommendationsmentioning
confidence: 99%